Drastic post‐LGM expansion and lack of historical genetic structure of a subtropical fig‐pollinating wasp ( Ceratosolen sp. 1) of Ficus septica in Taiwan - RONG‐CHIEN LIN; CAROL K‐L. YEUNG; SHOU‐HSIEN LI (Molecular Ecology, 2008)
The climatic oscillations of the last glacial period have had profound influences on the demography and levels of genetic diversity of extant species. Molecular evidence of glacial effects on temperate species has been well documented, whereas little is known regarding that on subtropical species. Here we present analyses based on partial sequences of the mitochondrial cytochrome c oxidase subunit I ( COI ) gene (1052 bp) and genotypes at 15 microsatellite loci to investigate the historical demography, population structure and ongoing gene flow of an undescribed fig‐pollinating wasp ( Ceratosolen sp. 1) of Ficus septica in subtropical Taiwan. Reconstructed historical demography based on the coalescent tree of COI sequences suggests that C . sp. 1 has undergone a drastic population expansion which was tightly coupled with climatic changes since the last glacial maximum (LGM). The magnitude of the population size change was approximately 500‐fold, indicating that the population of this wasp and its host was likely highly compressed during the last glacial period. The lack of significant population differentiation ( F ST F ST values) may be due to rapid postglacial expansion facilitated by long‐distance dispersal, although a low frequency of first‐generation migrants was detected. Our results clearly demonstrate how recent climatic changes since the LGM and dispersal ability have jointly shaped the genetic composition of a subtropical fig‐pollinating wasp.